Concept-Based Information Retrieval Approach - Sever, Hayri; Akal, Fuat; Köse, Güven (Information World, 2007)
Search engines become incompetent in tackling with the gap caused by differences in vocabularies used by both the authors of documents and users in expressing their information needs. One way to alleviate this problem is to introduce concept based retrieval of information. In this study, a model that can be regarded as an extension of RUBRIC system in some perspectives, but it has some distinct features especially suited for enabling descriptive-level retrieval was proposed and obtained results were evaluated.